MANAJEMEN PENGEMBANGAN KOMPETENSI DIGITAL GURU PAUD DALAM MENDESAIN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI - Niken Ayu Dwi Ardiyanti; Qausya Faviandhani (MOTORIC, 2026)
The development of digital technology requires Early Childhood Education (PAUD) institutions to be able to manage the improvement of teachers' digital competence in a targeted and sustainable manner. PAUD teachers are not only required to be able to use technological devices, but also to be able to design interactive learning media that are appropriate to the developmental characteristics of early childhood. This study aims to describe the management of ECE teachers' digital competence development in designing technology-based interactive learning media. The research focuses on planning teachers' digital competence development needs, implementing training or mentoring programs, utilizing digital applications in creating learning media, and evaluating the results of teacher competence development. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included ECE institution heads and ECE teachers involved in the use of digital learning media. The results are expected to demonstrate that the development of ECE teachers' digital competence needs to be managed through systematic managerial stages, starting from needs analysis, program planning, training implementation, practical mentoring, and evaluating the quality of the resulting learning media. Technology-based interactive learning media, such as interactive PowerPoint, Canva, Wordwall, educational videos, and simple learning applications, can support learning that is more engaging, visual, participatory, and appropriate to the world of children. Thus, managing the development of digital competencies in early childhood education (ECE) teachers is a crucial factor in improving the quality of learning, teacher creativity, and the readiness of ECE institutions to face the digital transformation of education. Keywords: ECE education management, teacher digital competency, interactive learning media, learning technology, ECE teachers